2014
DOI: 10.1038/cdd.2014.185
|View full text |Cite
|
Sign up to set email alerts
|

PTEN induces apoptosis and cavitation via HIF-2-dependent Bnip3 upregulation during epithelial lumen formation

Abstract: The tumor suppressor phosphatase and tensin homolog (PTEN) dephosphorylates PIP3 and antagonizes the prosurvival PI3K-Akt pathway. Targeted deletion of PTEN in mice led to early embryonic lethality. To elucidate its role in embryonic epithelial morphogenesis and the underlying mechanisms, we used embryonic stem cell-derived embryoid body (EB), an epithelial cyst structurally similar to the periimplantation embryo. PTEN is upregulated during EB morphogenesis in parallel with apoptosis of core cells, which media… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
36
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(38 citation statements)
references
References 48 publications
2
36
0
Order By: Relevance
“…1C, right). In agreement with previously published work (Qi et al, 2015), caspase-3 activation can be observed during embryoid body formation as early as 2 days after leukemia inhibitory factor (LIF) withdrawal, consistent with an increased apoptotic rate. We, however, noticed higher cleaved caspase-3 levels in GSKJ-4-treated day 2 embryoid bodies than in untreated cells (Fig.…”
Section: Inhibition Of Kdm6 Enzymatic Activity Leads To Cell Cycle Arsupporting
confidence: 80%
“…1C, right). In agreement with previously published work (Qi et al, 2015), caspase-3 activation can be observed during embryoid body formation as early as 2 days after leukemia inhibitory factor (LIF) withdrawal, consistent with an increased apoptotic rate. We, however, noticed higher cleaved caspase-3 levels in GSKJ-4-treated day 2 embryoid bodies than in untreated cells (Fig.…”
Section: Inhibition Of Kdm6 Enzymatic Activity Leads To Cell Cycle Arsupporting
confidence: 80%
“…In analogy to embryonic development, apoptosis occurs in floating embryoid body cultures during a process termed cavitation, which forms a proamniotic-like cavity (He et al, 2010;Qi et al, 2012). Bnip3, a BH3-only proapoptotic protein, is of key importance for this process (Qi et al, 2015). As Bnip3 was among the downregulated genes in our global expression analysis (Table S1), we consider it unlikely that normal differentiation was switched to a global proapoptotic program upon inhibition of KDM6 proteins.…”
Section: Discussionmentioning
confidence: 99%
“…Subsequent studies indicate that the defect in axis specification in CD1 background mutant embryos is caused by abnormal behavior of anterior visceral endoderm (AVE) cells, whereby Pten mutant AVE cells initiate movement but fail to migrate to the same extent as that in wild‐type embryos (Bloomekatz et al, ). In another study using the embryoid body model, the authors conclude that Pten is required for apoptosis‐mediated cavitation by regulating the expression of HIF‐2α and Bnip3, but not by suppression of PI3K or Akt (Qi et al, ), though these intriguing mechanisms were not tested or confirmed in embryos.…”
Section: Discussionmentioning
confidence: 99%